QUALITY OF LIFE OF PATIENTS ON CHRONIC HEMODIALYSIS PROGRAM IN THE CLINICAL CENTER OF MONTENEGRO - Peličić, Damir; Boljević,, Tanja; Raspopović, Milena; Saveljić, Mitar; Murić, Damira (HEALTH CARE, 2025)
Introduction/Aim: Health-related quality of life (HRQoL) is one of the key predictors of mortality and hospitalization in patients undergoing hemodialysis (HD) due to terminal kidney failure. The aim of our study was to examine the HRQoL of individuals with terminal chronic kidney disease who are undergoing HD at the Hemodialysis Center of the Clinical Center of Montenegro (CCM).Methods: A cross-sectional study included 43 participants with terminal chronic kidney disease who were on HD during January 2025 at the Hemodialysis Center of CCM. Data were collected from participants using a general and standardized anonymous questionnaire, the Kidney Disease Quality of Life Short Form (KDQOL-SF™) (Serbian version). Pearson's correlation coefficient was used for data analysis.Results: There is a significant negative correlation between the perception of success and satisfaction with the impact of kidney disease on daily activities (r = -0.45; p < 0.001). Satisfaction with treatment in HD patients is lower when the impact of kidney disease on their lives is greater (r = -0.47; p < 0.001). Sexual functioning issues are more pronounced when the impact of the disease on mental health is greater (r = 0.54; p < 0.001), as well as when there is more preoccupation with the disease during daily activities (r = 0.67; p < 0.001) and when the impact of kidney disease on life is greater (r = 0.46; p < 0.001).Conclusion: Further research is needed in this area to assess the quality of life of individuals with chronic kidney disease undergoing HD in relation to demographic and clinical parameters, as well as to identify independent predictors of quality of life.
Keywords: terminal kidney failure, chronic kidney disease, quality of life, hemodialysis